Syntagma „nazwa ptaka” + „dźwięki wydawane przezeń” w przekładach „Słowa o wyprawie Igora” na język rosyjski (na materiale równoległego korpusu przekładów „Słowa o wyprawie Igora”) - Słobodjan, Elena (Studia Rossica Posnaniensia, 2010)
In the multilingual Parallel corpus of translations of The Song of Igor's Campaign several translations of the literary monument into the same language are presented. The similar language material allows to solve many linguistic problems, in particular, allows to answer such questions as: which means of the given language (syntactical, morphological, lexical, figurative) can reflect the typical situation (for example, a situation of aural perception, a fight picture etc.); what lexicon is used to translate this or that concept; in what way lexemes function in the language and combine with each other; how the initial text influences language features of translation. The article consists an attempt to answer a part of these questions, concentrating on names of the sounds making by birds, and combination of these lexemes with names of birds on a material of Russian translations of The Song of Igor's Campaign.